Multilocular cystic leiomyoma of the anterolateral abdominal wall: A case report and literature review - Yorita, Kenji; Tanaka, Yu; Hirano, Koki; Kuwahara, Michio; Nakatani, Kimiko; Fukunaga, Masaharu; Agaimy, Abbas (Medicine, 2017)
RATIONALE: Leiomyomas arising from the anterolateral abdominal wall are uncommon, and their pathogenesis remains unknown. We present the 15th case of such a tumor, having this unique tumor morphology, followed by a detailed discussion on disease pathogenesis. PATIENT CONCERNS: A 48-year-old, asymptomatic perimenopausal, multiparous Japanese woman presented with a left-sided pelvic mass. She had no history of previous surgeries or uterine leiomyomas. Although a transabdominal ultrasonogram raised suspicions of an ovarian tumor, a transvaginal ultrasonogram confirmed normal ovaries. Radiological images showed a multilocular cystic mass with enhanced solid lesions connected to the uterus. Retrospective radiological evaluation showed that the mass was largely connected to the peritoneum of the anterolateral abdominal wall. INTERVENTIONS: Intraoperatively, the mass appeared as a dome-like protrusion from the left lower quadrant of the abdominal wall, without connection to the uterus, ovaries, or the left round ligament. No other peritoneal masses were seen. The mass was easily enucleated from the abdominal wall. Pathology confirmed that the mass was a leiomyoma with hydropic and myxoid degeneration. No striated muscle tissues were noted between the tumor and resection margin, but a thin smooth muscle layer, positive for hormone receptors, was present at the periphery, suggesting the origin of the tumor. LESSONS: Benign leiomyomas of the anterolateral abdominal wall likely originate from Müllerian-like smooth muscle remnants in this region. They should be considered in the differential diagnosis of solid and cystic masses and be distinguished from uterine and ovarian masses on imaging to avoid unnecessary organ resection.
EVALuna2:34889